Feasibility Study for the Development of Combination Dosage Form Containing Aspirin and Omeprazole for Treating Cardiovascular and Cerebrovascular Events (Bangladesh Pharmaceutical Journal, 2025)
Cardiovascular and cerebrovascular diseases are two of the major reasons of morbidity and mortality worldwide, hence require proper treatment and secondary prevention. Aspirin is a first line treatment option for the patients suffering from aforementioned issues and is usually co-administered with omeprazole to lessen the gastrointestinal side effects. A survey was done among patients, doctors, pharmaceuticals and retailers to explore the feasibility of developing a combination bilayer dosage form of aspirin and omeprazole so that the complications of co-administration can be minimized. Data were collected through direct interview and online questionnaire and statistical significance was determined using independent sample t-test. The study showed that drug utilization pattern of 85% of patients contain aspirin and omeprazole in the same prescription. Statistical data supported that both doctors and patients prefer the dose to be 75 mg for aspirin and 20 mg for omeprazole. More than 60% of each stakeholder showed their preference for the combination dosage form. Almost 50% of the doctors and patients preferred it for ease of consumption while retailers and manufactures considered the sales aspect. Moreover, ease of remembering, lesser number of pills consumption and lower price of the combination than the individual formulations came out to be the reasons for expecting availability of the combination among 68.82% of patients.  As the demand of the combination and the market prediction of the pharmaceuticals matched, so introduction of fixed dose aspirin-omeprazole bilayer combination in Bangladesh can be beneficial overall.Bangladesh Pharmaceutical Journal 28(1): 105-113, 2025 (January)